Git : mastering version control : learn everything you need to take full control of your workflow with Git with this curated Learning Path - dive in and transform the way you work : a course in three modules.: mastering version control : learn everything you need to take full control of your workflow with Git with this curated Learning Path - dive in and transform the way you work : a course in three modules. (2016) - Santacroce, Ferdinando; Olsson, Aske; Voss, Rasmus; Nare̜bski, Jakub
No abstract available